2019
DOI: 10.31557/apjcp.2019.20.11.3437
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Therapeutic Potential of Butein, A Tretrahydroxychalcone Against Human Oral Squamous Cell Carcinoma

Abstract: Background: Oral squamous cell carcinoma (OSCC) is one of the most predominant cancers in India. With advances in the field of oncology, a number of therapies have emerged; however, they are minimally effective. Consequently, there is a need to develop safe and effective regimens for the treatment of OSCC. Butein, a tetrahydroxychalcone has been found to exhibit potent antioxidant, anti-inflammatory, and also anti-tumor effects against several cancer types. However, its effect on OSCC is not studied yet. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…Various phytochemical and natural compounds obtained from different parts of plants have been a part of traditional medicine for ages and consumed for their health benefits as well as efficacy against a plethora of diseases [ [201] , [202] , [203] , [204] , [205] , [206] , [207] , [208] , [209] , [210] , [211] , [212] , [213] , [214] , [215] ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%
“…Various phytochemical and natural compounds obtained from different parts of plants have been a part of traditional medicine for ages and consumed for their health benefits as well as efficacy against a plethora of diseases [ [201] , [202] , [203] , [204] , [205] , [206] , [207] , [208] , [209] , [210] , [211] , [212] , [213] , [214] , [215] ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%
“…Zhang et al [ 200 ] found that ISL downregulated the expression of several MMPs including MMP-9 at mRNA as well as protein level. Additionally, suppression of MMP-9 expression has also been reported in butein-treated oral squamous cell carcinoma [ 102 ].…”
Section: Antiangiogenic Effects Of Chalconesmentioning
confidence: 99%
“…Butein, first isolated from the plant Oxicodendron vernicifluum, has been shown in a human oral squamous cancer cell line as an inhibitor of the phosphorylated form of NF-κB (p-p65). Moreover, butein also downregulated several NF-κB-regulated proteins such as the antiapoptotic factor survivin, COX-2, and adhesion molecule MMP-9 [ 102 ].…”
Section: Modulation Of Selected Signaling Pathwaysmentioning
confidence: 99%
“…The high incidence of OC in low resource countries is due to several customary habits such as alcohol consumption, smoking, tobacco chewing and areca nut chewing [10]. OC may also occur due to human papillomavirus (HPV) infection, poor dental care, poor hygiene and consumption of unhealthy food.…”
Section: Introductionmentioning
confidence: 99%